Mathematics and statistics paper-I XII science - Jadhav B.P., Patawardhan P.D., Kasarekar R.T., Kubade M.K. Aithal & etc. (Phadake publications,Kolhapur, 2007)
Stats/Maths
ENGLISH
Keywords: Mathematics and statistics paper-I XII science; Stats/Maths; Stats/Maths